Reconstruction of the Game and Rules of the Batu Dampar Game - Syaryani Husein Lubis; Nurhayati Simatupang; Indra Kasih (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to reconstruct the game and the rules of the Batu Dampar game so that it can become a standard game and rules. This type of research is development research based on the ADDIE Model. The test subjects consisted of material experts, game experts, media experts and resource persons. The first stage of this model is the needs research stage, followed by the design stage and the third stage is development and implementation. In this stage, all stages involve an evaluation and revision process. The assessment of language experts is 93% with very good criteria, for game experts it is 93.27% with very good criteria and the results of the assessment of sports teachers are 87.3%. And media expert 88.3 with very good criteria. In the results of the data triangulation test, it was found that the similarity of the data from the sources with the referenced theory. As well as the data collected from resource persons who are used as a reference for product development, then an assessment is made to experts and users through an assessment questionnaire, the results of the assessment have increased and the response has been positive in every test carried out. In accordance with the criteria and presentation of the results of the assessment carried out through a questionnaire.